Democracy in Divided Societies: Electoral Engineering for Conflict Management “Chapter 3 Centripetal Incentives and Political Engineering in Australia” - Muharam, Ricky Santoso (Jurnal Sosioteknologi, 2024)
Benjamin Reilly is a professor of political science and international relations at the University of Western Australia. Benjamin previously served as dean of the Sir Walter Murdoch School and was director of the Centre for democratic institutions at the Australian National University (ANU). Benjamin is also an expert in the Australian government, the United Nations, and other international organizations. As a professor of political science, Benjamin was invited to various scientific forums to speak at well-known campuses, such as Harvard, Oxford, and Johns Hopkins. Publicizing scientific papers and books earned Benjamin numerous international grants from the Carnegie Corporation of New York, the United StatesInstitute of Peace, the East-West Center, the National Endowment for Democracy, and the Australian Research Council. Benjamin’s ideas and thoughts were widely published in various international and national newspapers, including the New York Times, Financial Times, Wall Street Journal, Washington Post, and Time Magazine.